Pengaruh Abu Pembakaran Sampah Dengan Penambahan Kotoran Kijang Untuk Pupuk Tanaman Hias - Moch Zainuri; Yanatra Budi Pramana; Arif Yachya; Manik Ayu Titisari; Ida Kusnawati Tjahjani; Krisyanti Budipramana; Suparman (Universitas PGRI Adi Buana Surabaya, 2025)
The increasing volume of waste in Indonesia poses environmental challenges, especially incinerator ash residues that contain heavy metals and have the potential to contaminate soil. This study aimed to evaluate the utilization of incinerator ash combined with deer dung as an alternative growing medium for ornamental betel nut (Epipremnum aureum). Four treatments of growing media composition were tested: pure soil, ash and dung mixture in different ratios, and observed for eight weeks on the parameters of plant length, leaf area, and plant weight. Results showed that the treatment without ash mixture produced the best growth, while increasing the proportion of ash decreased plant growth performance. This is thought to be due to the heavy metal content in the ash which inhibits plant metabolism and nutrient uptake. Although the plants survived in all treatments, the effectiveness of the ash and deer manure mixture as a growing medium proved to be limited, so its use should be limited and not recommended for consumption crops. The potential utilization of ash is more appropriately directed towards non-agricultural sectors that do not come into direct contact with living things.